AESTHETIC IDEAL IN GHAFUR GHULAM'S STORIES - Muratova Gulbakhar (American Journals, 2023)
This article examines the famous Uzbek writer Gafur Ghulam's story "My son of a thief". This story analysis example analyzes the uniqueness of the writer's skill. Opinions about G. Ghulam's heroic spiritual experiences, expression of the uniqueness of human nature are put forward. Opinions advanced in the article are generalized to a certain extent.
Keywords: Character, prose, story, image, artistic expression, originality. artistic skill, aesthetic ideal, national spirit.